(untitled) (Afaq Lughawiyyah, 2024)
The grammatical rules are one of the most important topics in learning Arabic. Mastering all morphological rules deeply enhances Arabic language skills. The inability to grasp these rules among students indicates a failure in mastering the Arabic language. This research aims to address this issue by identifying challenges faced by students in not mastering morphological rules and also by identifying strategies to overcome them. The researchers employed a quantitative approach through the survey method. They distributed questionnaires to fourth-grade students at Ma’ahad Madinatul Huffaz, Selangor, to collect data related to the research topic. Subsequently, the researchers inputted the data into SPSS software to identify the major difficulties in mastering morphological rules among these students, as well as to recognize the most commonly used strategies to overcome these difficulties. The results indicated that the biggest challenge was the perception that morphological rules are difficult, with an average score of 2.90. As for the most used strategies to overcome these difficulties, asking questions related to morphological topics to teachers or knowledgeable friends scored an average of 4.08.